35Cl–1H Heteronuclear correlation magic‐angle spinning nuclear magnetic resonance experiments for probing pharmaceutical salts. (14th July 2021) - Iuga, Dinu; Corlett, Emily K.; Brown, Steven P.
Abstract: Heteronuclear multiple‐quantum coherence (HMQC) pulse sequences for establishing heteronuclear correlation in solid‐state nuclear magnetic resonance (NMR) between 35 Cl and 1 H nuclei in chloride salts under fast (60 kHz) magic‐angle spinning (MAS) and at high magnetic field (a 1 H Larmor frequency of 850 MHz) are investigated. Specifically, recoupling of the 35 Cl– 1 H dipolar interaction using rotary resonance recoupling with phase inversion every rotor period or the symmetry‐based SR4 2 1 pulse sequences are compared. In our implementation of the population transfer (PT) dipolar (D) HMQC experiment, the satellite transitions of the 35 Cl nuclei are saturated with an off‐resonance WURST sweep, at a low nutation frequency, over the second spinning sideband, whereby the WURST pulse must be of the same duration as the recoupling time. Numerical simulations of the 35 Cl– 1 H MAS D‐HMQC experiment performed separately for each crystallite orientation in a powder provide insight into the orientation dependence of changes in the second‐order quadrupolar‐broadened 35 Cl MAS NMR lineshape under the application of dipolar recoupling. Two‐dimensional 35 Cl– 1 H PT‐D‐HMQC MAS NMR spectra are presented for the amino acids glycine·HCl and l ‐tyrosine·HCl and the pharmaceuticals cimetidine·HCl, amitriptyline·HCl and lidocaine·HCl·H2 O. Experimentally observed 35 Cl lineshapes are compared with those simulated for 35 Cl chemical shift and quadrupolar parameters as calculated using the gauge‐including projector‐augmented wave (GIPAW) method: the calculated quadrupolar product ( P Q ) values exceed those measured experimentally by a factor of between 1.3 and 1.9. Abstract : 35 Cl– 1 H HMQC MAS NMR: The graphic shows the scaling factor for all orientations in a powder of a 35 Cl nucleus coupled to a 1 H nucleus for 35 Cl– 1 H SR4 2 1 recoupling and the effect of recoupling on the MAS second‐order quadrupolar broadened lineshape.